Parents' perceptions about child abuse and their impact on physical and emotional child abuse: A study from primary health care centers in Riyadh, Saudi Arabia - Mohammed N Al Dosari; Mazen Ferwana; Imad Abdulmajeed; Khaled K Aldossari; Jamaan M Al-Zahrani (Wolters Kluwer Medknow Publications, 2017)
OBJECTIVE: To determine perceptions of parents about child abuse, and their impact on physical and emotional child abuse. MATERIALS AND METHODS: Two hundred parents attending three primary health care centers (PHCCs) in Riyadh serving National Guard employes and their families, were requested to participate in this survey. Data was collected by self administered questionnaire. Five main risk factors areas/domains were explored; three were parent related (personal factors, history of parents' childhood abuse, and parental attitude toward punishment), and two were family/community effects and factors specific to the child. SPSS was used for data entry and analysis. Descriptive analysis included computation of mean, median, mode, frequencies, and percentages; Chi-square test and t-test were used to test for statistical significance, and regression analysis performed to explore relationships between child abuse and various risk factors. RESULTS: Thirty-four percent of the parents reported a childhood history of physical abuse. Almost 18% of the parents used physical punishment. The risk factors associated significantly with child abuse were parents' history of physical abuse, young parent, witness to domestic violence, and poor self-control. Child-related factors included a child who is difficult to control or has attention deficit hyperactivity disorder (ADHD). Parents who did not own a house were more likely to use physical punishment. Abusive beliefs of parent as risk factors were: physical punishment as an effective educational tool for a noisy child; parents' assent to physical punishment for children; it is difficult to differentiate between physical punishment and child abuse; parents have the right to discipline their child as they deem necessary; and there is no need for a system for the prevention of child abuse. CONCLUSION: The causes of child abuse and neglect are complex. Though detecting child abuse may be difficult in primary care practice, many risk factors can be identified early. Parents' attitudes can be measured, and prevention initiatives, such as screening and counseling for parents of children at risk, can be developed and incorporated into primary care practice.